O uso de drogas na consumação da modernidade - Ong, Lucas Francis e Silva (2015)
Drug use pervades the history of mankind since its inception. However, the current situation is quite peculiar: the recent prohibitionist policy on War on Drugs, the synthesis of psychoactive principles and unrestrained production of new drugs are just some of the facts that converge with a staggering abuse, compulsion and dependence, setting up a significant increase in drug use over the past decades. To understand the use of drugs in Modernity, the traditional scientific approach is not sufficient, because it proceeds from the sectioning of this phenomenon, dismantling it from the broader historical event in which it is originally immersed. Through Martin Heidegger's hermeneutic phenomenology, the aim is to understand the current relationship between man and drugs, directly marked by the event of Modernity: technique